Republic of Moldova : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
This first Country Procurement Assessment Report (CPAR) on Moldova comes at a time when the country has publicly committed itself to the signal departure of acceding to the WTO Agreement o n Government Procurement (GPA). It will be the first developing country in Eastern Europe t o do so. The CPAR's key findings, including risk assessment, the strengths and weaknesses of the public procurement system currently in place, and the main features of a proposed action plan are summarized here. Public procurement represents a substantial element of the expenditure side of the Government's budget. Estimates prepared for this assessment indicate that total expenditure on procurement amounted to approximately US$118 million. Procurement accounted for 17 percent of total expenditures by the State government and 42 percent of expenditure by local governments, with expenditure at all levels showing substantial increases over past years. Improving the efficiency of that expenditure can contribute to better budget management. Yet control of public procurement expenditures in Moldova is weak and the overall procurement environment is high- risk. While the procurement law provides a reasonably sound basis for public procurement, and will need to be amended to align it with the WTO Agreement on Government Procurement. I t is further undermined by the absence of implementing regulations. Procurement practices are often inconsistent with the procurement law, Primary among these is the heavy overuse of the Single Source Procurement method, whereby the procuring entity contracts directly with a single supplier, with n o competition. Weaknesses in the law permit other bad practices. Resources: While the NAGP is seen as providing a valued service to procuring entities and is progressively extending its coverage, its reach is limited at the local government level. However, the Agency is not being held accountable for its performance of its regulatory and oversight functions and, because it is one of the bodies which makes the Government's decisions on procurement, it cannot act independently when reviewing bid protests. Procuring entities lack the capacity to conduct procurement effectively and in accordance with the procurement law, and there is political interference in procurement decision making. The report recommends that The current procurement law should be amended, and the Government should enact a comprehensive set of implementing regulations to underpin the law. The position of Executive Director of the NAGP should be filled immediately. The NAGP should be held more accountable for the performance of its functions. New institutional arrangements should be made for the independent review of bid protests It is necessary to build public sector capacity to undertake public procurement As a short-term action, given the urgent need to train the dedicated procurement staff of the 35 recently establish territorial administrative units, the NAGP should conduct training courses in public procurement for those units by the end of 2003.